Case Report: Delayed-type hypersensitivity reaction to meropenem in an elderly patient—successful management with imipenem-cilastatin - He, Cuilin; Liu, Maozhu; Ye, Jiao; Zheng, Hong; Yang, Junjie; Huang, Lingmei (Frontiers in Medicine, 2025)
Meropenem is a clinically essential carbapenem antibiotic with a broad antimicrobial spectrum, potent antibacterial efficacy, and high stability against β-lactamase, which plays a pivotal role in anti-infective therapy. In clinical practice, meropenem generally shows a favorable safety and tolerability profile, with relatively few reports of serious adverse reactions. Here, we present a case of an 80-year-old woman who developed a delayed-type hypersensitivity (DTH) reaction after receiving anti-infective treatment with meropenem. This allergic reaction was immediately managed with calcium gluconate, dexamethasone sodium phosphate, and ebastine. Meanwhile, meropenem was discontinued and replaced with imipenem-cilastatin to control the infection. Following a 14-day antimicrobial therapy, initially with imipenem-cilastatin and subsequently with amoxicillin-clavulanate potassium tablets, the patient’s skin rashes gradually subsided and the infection was successfully controlled. This case highlights the risk of DTH reaction induced by meropenem in clinical settings. Clinicians should remain vigilant for DTH reactions during meropenem therapy and cautiously consider alternative carbapenems such as imipenem-cilastatin.